Pre-pregnancy cardiometabolic markers with early childhood weight – A systematic review. - Baluswami, Dr. Gayathri; Shunmugavelu, Dr.Karthik (Student's Journal of Health Research Africa, 2024)
Background Pregnancy involves complex metabolic and cardiovascular adaptations that support fetal growth. Suboptimal cardiometabolic health before conception may predispose offspring to altered growth trajectories and increased risk of obesity in early childhood. With rising maternal age and increasing prevalence of obesity, diabetes, and hypertension, understanding pre-pregnancy cardiometabolic markers has become essential for intergenerational health prevention. Objective: To systematically evaluate the association between pre-pregnancy cardiometabolic markers and early childhood weight outcomes. Methods A systematic review was conducted following PRISMA guidelines. Electronic databases, including PubMed, MEDLINE, Embase, Scopus, Web of Science, and LILACS, were searched for studies published between 2020 and 2024. Observational studies assessing pre-pregnancy cardiometabolic markers and offspring weight outcomes were included. Results Eight eligible studies were included. Across cohorts, elevated pre-pregnancy body mass index, dyslipidemia, impaired glucose metabolism, and hypertensive markers were consistently associated with higher birth weight, accelerated infant weight gain, and increased risk of overweight or obesity in early childhood. These associations persisted after adjustment for sociodemographic factors and, in several studies, were independent of genetic predisposition. Evidence also suggested that combined cardiometabolic risk factors exert stronger effects than isolated markers, supporting an intrauterine programming mechanism. Conclusion Pre-pregnancy cardiometabolic health is strongly associated with early childhood weight outcomes. The findings identify the pre-conception period as a critical window for intervention to reduce intergenerational cardiometabolic risk. Future research Prospective studies incorporating standardized biomarker panels, sex-specific offspring analyses, and long-term follow-up into adolescence are needed to strengthen causal inference.